Multiprocessors Interconnection Networks - El‐Rewini, Hesham; Abd‐El‐Barr, Mostafa (Advanced Computer Architecture and Parallel Processing, 2004)
In this chapter, we introduce the different topologies used for interconnecting multiple processors and memory modules. Two schemes are introduced, namely static and dynamic interconnection networks. Static networks form all connections when the system is designed rather than when the connection is needed. In a static network, messages must be routed along established links. Dynamic interconnection networks establish connections between two or more nodes on the fly as messages are routed along the links. The hypercube, mesh, and k‐ary n‐cube topologies are introduced as examples for static networks. The bus, crossbar, and multi‐stage interconnection topologies are introduced as examples for dynamic interconnection networks. Our coverage in this chapter concludes with a section on performance evaluation and analysis of the different interconnection networks.